Helping primary care providers recognize and respond to medication non-adherence and drug-drug interactions: A randomized-controlled clinical utility trial in a value-based care setting - Trever Burgon; David Paculdo; Joshua Schrecker; Kelsy Gibson Ferrara; Randy E. David; Steven Johnson; Czarlota Valdenor; John W. Peabody (PLoS ONE, 2026)
Objective To determine the clinical utility of a novel chronic disease management test among primary care providers practicing in a value-based care setting. The study assessed the ability of primary care providers to recognize and respond to medication nonadherence (MNA), drug-drug interactions (DDIs), and disease progression. Design A pre-post experimental randomized controlled trial of primary care providers in the same practice setting caring for simulated patients with chronic disease. Setting and participants 139 licensed primary care providers (MD, DO, NP, or PA) at a large, multi-state primary care practice in the United States. Intervention Both intervention and control group participants cared for three simulated chronic disease patients at baseline and again after the intervention. After baseline, intervention group participants reviewed educational materials about a new saliva-based chronic disease management test that detects MNA and DDI and were then provided with the test’s results in simulation; the control group did not have access to the test results. Primary outcome measures Changes in care decisions between the two groups were analyzed using a difference-in-differences approach to determine whether routine testing in the outpatient setting changed correct identification and management of medication nonadherence (MNA), drug-drug interactions (DDI), and disease progression. Results The intervention group participants were significantly more likely to make the correct diagnosis of MNA (control: 10.0% vs intervention: 80.0%, p < 0.001) and DDI (control: 18.6% vs intervention: 52.9%, p < 0.001) and to recommend an appropriate treatment for MNA (control: 25.7% vs intervention: 54.3%, p = 0.001) and DDI patients (control: 27.1% vs intervention: 58.8%, p < 0.001). Conclusion Primary care providers with results from a definitive saliva-based test for MNA and DDI were significantly more likely to identify those common challenges and make appropriate updates to the patient’s treatment plan. This has important implications for improving quality and value, especially for the millions of patients with chronic conditions on multiple medications. Trial registration ClinicalTrials.gov, NCT05658653, Registered 2-Dec-2022.